2018
DOI: 10.1111/imcb.12020
|View full text |Cite
|
Sign up to set email alerts
|

Human MAIT cells show metabolic quiescence with rapid glucose‐dependent upregulation of granzyme B upon stimulation

Abstract: Mucosal‐associated invariant T (MAIT) cells are a well‐characterized innate‐like T cell population abundant in the human liver, peripheral tissues and blood. MAIT cells serve in the first line of defense against infections, through engagement of their T cell receptor, which recognizes microbial metabolites presented on MR1, and through cytokine‐mediated triggering. Typically, they show a quiescent memory phenotype but can undergo rapid upregulation of effector functions including cytolysis upon stimulation. T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 31 publications
3
44
0
Order By: Relevance
“…Once activated, MAIT cells show their effector functions, including producing cytokines and inducing cytolysis. Sometimes these processes were accompanied with the increasing uptake of glucose [44]. Furthermore, it was also reported that the mTORC1 signaling was relevant to the glycolysis of MAIT cells, leading to altered MAIT cell responses [45].…”
Section: Ivyspringmentioning
confidence: 99%
“…Once activated, MAIT cells show their effector functions, including producing cytokines and inducing cytolysis. Sometimes these processes were accompanied with the increasing uptake of glucose [44]. Furthermore, it was also reported that the mTORC1 signaling was relevant to the glycolysis of MAIT cells, leading to altered MAIT cell responses [45].…”
Section: Ivyspringmentioning
confidence: 99%
“…Zinser et al . Human MAIT cells show metabolic quiescence with rapid glucose‐dependent upregulation of granzyme B upon stimulation Cameron & Godfrey.…”
mentioning
confidence: 99%
“…Another key topic covered in our top 10 publications is the identification and characterization of innate and innate‐like lymphocytes including innate lymphoid cells (ILC), mucosal‐associated invariant T (MAIT) cells, and natural killer T (NKT) cells . The study by Steigler et al .…”
mentioning
confidence: 99%
See 2 more Smart Citations